(Azulene‐1, 3‐diyl)‐bis(nitronyl nitroxide) and (Azulene‐1, 3‐diyl)‐bis(iminonitroxide) and Their Copper Complexes. Issue 22 (31st October 2017) - Haraguchi, Makoto; Tretyakov, Evgeny; Gritsan, Nina; Romanenko, Galina; Gorbunov, Dmitry; Bogomyakov, Artem; Maryunina, Kseniya; Suzuki, Shuichi; Kozaki, Masatoshi; Shiomi, Daisuke; Sato, Kazunobu; Takui, Takeji; et al.
Abstract: In contrast to diradicals connected by alternant hydrocarbons, only a few studies on those connected by nonalternant hydrocarbons have been reported. The syntheses, structures, and magnetic properties of azulene‐1, 3‐diyl linked bis(nitronyl nitroxide) (NN2 Az) and bis(iminonitroxide) (IN2 Az) diradicals and their Cu(hfac)2 (hfac=hexafluoroacetylacetonate) complexes were investigated. NN2 Az was shown to have an intramolecular ferromagnetic interaction with J obs / k B =+10.0 K ( H =−2 J S 1 ⋅S 2 ) between (nitronyl nitroxide) spins, whereas IN2 Az was estimated to have a much weaker intramolecular magnetic interaction. The reactions of NN2 Az and IN2 Az with Cu(hfac)2 gave a 1:2 [Cu(hfac)2 2 (NN2 Az)] complex and a 1:1 [Cu(hfac)2 (IN2 Az)]⋅ C6 H12 complex, respectively. [Cu(hfac)2 2 (NN2 Az)] showed strong intramolecular antiferromagnetic interactions ( J 1‐Cu‐R / k B ≈−800 K, J 2‐Cu‐R / k B ≈−500 K) between the Cu II spins and the coordinating NN spins, whereas [Cu(hfac)2 (IN2 Az)] exhibited a ferromagnetic exchange interaction ( J obs‐Cu‐R / k B =+114 K) between the Cu II spin and the imino‐coordinated iminonitroxide spin. Abstract : Nonalternant exchange : Bis(nitronyl nitroxide) and bis(iminonitroxide) diradicals linked by a nonalternant azulene‐1, 3‐diyl coupler (i.e., NN2 Az and IN2 Az, respectively) and their Cu(hfac)2 (hfac=hexafluoroacetylacetonate) complexes, [Cu(hfac)2 2 (NN2 Az)] and [Cu(hfac)2 (IN2 Az)], are synthesized and their magnetic properties are investigated.